A hybrid method to characterize the mechanical behaviour of biological hyper-elastic tissues - Ribeiro, J.E. (2014)
The increase of interest in the study of human biological tissues led to the characterization of certain biological materials which have a hyper-elastic mechanical behaviour. Traditionally are used experimental tests to characterize such materials, however, these have been replaced by numerical simulations using finite element codes, with advantages from the point of view of saving time and financial costs. The optical experimental field methods have the advantage, such as the assessment of displacement fields without contact with high resolution, using ordinary white light or laser illumination. Both techniques, experimental and numerical, have limitations in the characterization of hyper-elastic biological tissues. The numerical simulation has different constitutive models, but none of them could characterize completely these materials. In the other hand, most of the optical techniques have a high sensibility which is not adequate for hyper-elastic behaviours. Only the digital image correlation (DIC) has the sensibility range that could allow the measurement of such large displacements. However, the strain fields are computed by the differentiation of displacement fields and this technique could amplify the image noise, in this case the quality of strain fields are not adequate. To overcome these limitations the authors of this work have developed a hybrid method which uses the displacement field obtained with DIC applied in the nodes of a finite element model.